Hype or Hope: Digital Technologies in Auditing Process - Allbabidi, Mohamad Hesham Adnan (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study aims to examine how technological,organisational and environmental (TOE) factors affect digital technologies’ utilisation and its impact on auditors’ performance. Design/Methodology/Approach: A survey was conducted on 4 large and non-large companies in Jordan, and data were retrieved from 168 external auditors. The partial least squares (PLS-3) structural equations modeling was used to analyse data and to test the proposed model. Research findings: Results show that the TOE factors have a significant and positive effect on digital technologies utilisation. It also appears to enhance auditors’ performance. Theoretical contribution/Originality: This study fills a gap in the literature of accounting by empirically assessing how digital technologies utilisation impacts the performance of auditors in Jordan. It also expands on previous literature by determining how the TOE factors affect such technology usage in the auditing process. This study also has a methodological contribution in the form of measuring the client’s complexity of IT system from a different perspective, which is from the external auditor’s perspective. Practitioner/Policy implications: This study is expected to help regulators and audit companies to update their policies and regulations so that auditors are trained in using advanced technologies, and in protecting the security of accounting information. In this regard, efficient auditors will be able to protect investors, thereby creating an attractive environment for investment which can boost economic growth. Research limitation/Implications: This study is based on the Jordanian context. There was no comparison made with developing or developed countries, hence no distinctions can be detected. Future studies should focus on looking at other countries so as to provide new insights into the auditing profession, and specifically, auditors’ performance. Finally, this study is a practical guide for external and internal auditors who have not considered digital technologies, in the context of Jordan. Future studies may thus consider internal auditors and their relationship with external auditors in digital technologies utilisation. Keywords: Technological, Organisational and Environmental Factors, Auditors’ Performance, Digital Technologies JEL Classification: M42